Beyond “Net-Zero”: A Case for Separate Targets for Emissions Reduction and Negative Emissions - McLaren, Duncan P.; Tyfield, David P.; Willis, Rebecca; Szerszynski, Bronislaw; Markusson, Nils O. (Frontiers in Climate, 2019)
• Targets and accounting for negative emissions should be explicitly set and managed separately from existing and future targets for emissions reduction. • Failure to make such a separation has already hampered climate policy, exaggerating the expected future contribution of negative emissions in climate models, while also obscuring the extent and pace of the investment needed to deliver negative emissions. • Separation would help minimise the negative impacts that promises and deployments of negative emissions could have on emissions reduction, arising from effects such as temporal trade-offs, excessive offsetting, and technological lock-in. • Benefits for international, national, local, organisational and sectoral planning would arise from greater clarity over the role and timing of negative emissions alongside accelerated emissions reduction.